Cardiac arrest in a patient with anterior fascicular block after administration of dexmedetomidine with spinal anesthesia: A case report. Issue 43 (October 2016) - Kim, Baek Jin; Kim, Bong Il; Byun, Sung Hye; Kim, Eugene; Sung, Shin Yeung; Jung, Jin Yong
Abstract: Background: Dexmedetomidine is a sedative and analgesic agent that is administered intravenously as an adjunct to spinal anesthesia. It does not suppress the respiratory system significantly, but has adverse effects on the cardiovascular system, for example, bradycardia and hypotension. We here report a patient who underwent cardiac arrest during spinal anesthesia after intravenous infusion of dexmedetomidine. Methods: A 57-year-old woman with no significant medical history underwent spinal anesthesia for arthroscopic meniscus resection after rupturing the right knee meniscus. Preoperative electrocardiogram revealed sinus bradycardia (54 beats/min) and a left anterior fascicular block. Spinal anesthesia was performed with 11 mg of 0.5% heavy bupivacaine, and the upper level of sensory loss was at T6. Dexmedetomidine infusion was planned at a loading dose of 1.0 mcg kg −1  min −1 over 10 minutes, followed by 0.7 mcg kg −1  min −1 intravenously, as a sedative. Two minutes after dexmedetomidine injection, her heart rate decreased to 31 beats/min and asystole was observed within 10 seconds. Results: After a few minutes of cardiopulmonary resuscitation, spontaneous circulation returned and surgery was completed under general anesthesia. The patient was discharged, and experienced no complications. Conclusion: Dexmedetomidine can decrease blood pressure and heart rate, and may cause asystole in some cases. We suggest that dexmedetomidine should be carefully administered under close observation when the parasympathetic nerve system is activated during spinal anesthesia.